Halal and Muslim-Minority Countries: A Systematic Literature Review - Khairul Akmaliah Adham; Nur Sa’adah Muhamad; Mohd Fuaad Said; Nadiah Mahmad Nasir (Faculty of Business and Economics, University of Malaya, 2024)
Indexed by Scopus